2019
DOI: 10.3390/ijerph16204028
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Health Conditions, Consciousness, Involvement, and Knowledge and Dietary Supplement Intake among University Students in South Korea

Abstract: Dietary supplements (DSs) are typically used by the elderly in a population, but younger age groups are increasingly purchasing these products. In consideration of this issue, the present study investigated the DS-related behaviors and general lifestyles of university students in South Korea. The health conditions, consciousness, involvement, and knowledge, as well as the future behavioral intentions, of DS users and non-users were determined and compared. A survey was administered to the respondents, and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Our study also revealed that 41% of the online learning undergraduates consumed health supplements, and parents were found to be their main adviser in taking the supplements. A same phenomenon was reported by Choi [ 26 ], in which the majority (49.7%) of the university students consumed supplements according to the suggestions given by their family members. To boost their immune system, a high proportion of Indonesian university students (67.7%) consumed supplements such as multivitamins during the COVID-19 pandemic [ 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…Our study also revealed that 41% of the online learning undergraduates consumed health supplements, and parents were found to be their main adviser in taking the supplements. A same phenomenon was reported by Choi [ 26 ], in which the majority (49.7%) of the university students consumed supplements according to the suggestions given by their family members. To boost their immune system, a high proportion of Indonesian university students (67.7%) consumed supplements such as multivitamins during the COVID-19 pandemic [ 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…Similar to those previously reported in other studies [ 5 , 10 , 18 , 19 ], the most commonly consumed dietary supplements in Korea were vitamin and mineral (61.41%), omega-3 fatty acid (11.85%) and probiotics (pre-, post-) (4.72%). However, the important difference is that Koreans prefer to consume ginseng and red ginseng compared with people in other countries (7.99%).…”
Section: Discussionsupporting
confidence: 87%
“…This is because most dietary supplements are not classified as drugs by the Food and Drug Administration and are easily obtainable with unrestricted exposure to advertisements. Dietary supplement intake data from the Korean National Health and Nutrition Examination Survey (KNHANES) also showed that approximately 42% of Korean adults aged ≥19 years have taken a dietary supplement at least once in their lifetime [ 10 ]. However, the role of dietary supplements is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with some other studies [50], the findings in this study favor gender-specific intervention programs for adolescents to instill knowledge on correct and wise usage of DS. Moreover, a risk of misuse of DS among children and adolescents [51] warrant educational intervention for correct and wise usage and better public health.…”
Section: Discussionmentioning
confidence: 99%